Peran Pengembangan Desa Wisata dalam Upaya Peningkatan Keberlangsungan Ekonomi kreatif Masyarakat di Kabupaten Kerinci - Dontes Putra (STAIN MAJENE, 2024)
The development of tourist villages aims to increase village original income (PADes) and create a prosperous village community through increasing the sustainability of the community's creative economy. This research aims to analyze the role of developing tourist villages in efforts to increase the sustainability of the creative economy of the community in Kerinci Regency. This research is field research with a qualitative descriptive approach. The informants in this research were the government, tourism village managers, the community, and creative economy actors in Kerinci Regency, as many as 45 people. The selection of informants used purposive sampling. Data collection techniques include observation, interviews, and documentation. Data is processed using data reduction techniques, data presentation, and drawing conclusions. The results of this research show that the government plays a role in developing tourist villages through tourism planning, development of tourism destinations, and tourism policies and regulations. The development of a tourist village is supported by a natural village atmosphere, the community as the host of a tourist village, the cohesiveness of the youth organization, and adequate facilities and transportation accessibility. However, the development of tourist villages is hampered by the lack of maintenance of supporting facilities for tourist village objects, inadequate quality of human resources (HR), lack of promotional efforts, lack of community-based empowerment, and parking services and facilities. Therefore, the government carries out guidance, monitoring, and training. Apart from that, the government acts as a facilitator, uses promotional media, and organizes creative economy festivals and exhibitions. Thus, government policies have a significant impact on creative economy actors, such as financial support, ease of licensing, Keywords: Development of Tourism Villages, Role of Government, Sustainability of the Creative Economy